2015
DOI: 10.1111/ijd.12974
|View full text |Cite
|
Sign up to set email alerts
|

Terra firma‐forme dermatosis: report of a series of 11 cases and a brief review of the literature

Abstract: Awareness among the clinicians about the existence of TFFD is essential to save time for the clinician and to reduce the economic burden on the patient by avoiding costly investigations and treatment. Proper counseling regarding the cleansing of surgery sites may help prevent the development of this condition in such situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 22 publications
0
20
0
1
Order By: Relevance
“…Despite these differences, the distinction between DN and TFFD becomes difficult at times and it seems that there exists clinical and histological overlap between the two conditions 3,4,6,7,9,10,13 . Some authors have suggested that the difference between TFFD and DN is arbitrary and TFFD may be a milder form of DN 14 . TFFD can simulate many dermatoses ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Despite these differences, the distinction between DN and TFFD becomes difficult at times and it seems that there exists clinical and histological overlap between the two conditions 3,4,6,7,9,10,13 . Some authors have suggested that the difference between TFFD and DN is arbitrary and TFFD may be a milder form of DN 14 . TFFD can simulate many dermatoses ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Asslan et al two patients were siblings and had xerosis, which may lead to a suspicion of the possible impact of inheritance on the occurrence of this disease, but more extensive studies are needed to confirm these assumptions (7). As a possible cause of TFFD, Ashique et al emphasize inadequate hygiene and inappropriate care of skin areas damaged by previous surgical interventions (13). Most of other authors did not establish a relationship of TFFD with poor hygiene or hygienic habits (3,10,12,13).…”
Section: Discussionmentioning
confidence: 99%
“…As a possible cause of TFFD, Ashique et al emphasize inadequate hygiene and inappropriate care of skin areas damaged by previous surgical interventions (13). Most of other authors did not establish a relationship of TFFD with poor hygiene or hygienic habits (3,10,12,13). Patients often state that the changes occurred during warm periods and sometimes due to the intense exposure to the sun (1,8,10,12,14).…”
Section: Discussionmentioning
confidence: 99%
“…Verriköz plakların keratinosit olgunlaşmasındaki bozulma sonucunda melanin retansiyonuna ek olarak sebum, ter ve mikroorganizmaların İzmir Dr. Behçet Uz Çocuk Hast. Dergisi 2017; 7 (2): [167][168] birikimi ile oluştuğu öne sürülmektedir (7) . Son üç aydır dış merkezde takip edilen on beş yaşındaki obez erkek hastanın lezyonları, aile öyküsünde diyabetes mellitus olması üzerine, akantozis nigrigans olarak değerlendirilmiş.…”
unclassified